Synergism activity between Moringa oleifera and Azadirachta indica crude extracts against Nilaparvata lugens (Hemiptera: Delphacidae) - Mohd Mohkheri, Muhammad Nabil Fariq (Universiti Kebangsaan Malaysia. Pusat Sistematik Serangga,National University of Malaysia. Centre for Insect Systematics, 2021)
Extract seeds of Moringa oleifera and Azadirachta indica were tested separately and in mixture (1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1) in the laboratory for their insecticidal activity against Nilaparvata lugens (Hemiptera: Delphacidae). Moringa oleifera and A. indica plant materials were extracted with hexane using maceration technique. Insecticidal bioassays were done by leaf-dip bioassays method. Second to fourth instar nymph of N. lugens were fed extract treated paddy seedling and were observed for 24, 48 and 72 hours. The data were analyzed using PoloPlus V.2 program, analysis of variance (ANOVA) and CompuSyn software. The results showed that the yield of extraction for M. oleifera was 26.7%, while for A. indica was 3.0%. Based on LC50 value, mixture extract (3:7) of M. oleifera and A. indica (LC50=52.24 mg/L) were more toxic compared to other mixture ratios and single crude of M. oleifera (98.03mg/L) and A. indica (87.45mg/L). Based on mortality percentages at 72 hours, 0.05% mixture of M. oleifera and A. indica showed good efficacy against nymph of N. lugens with 74.81% compared to 0.025% and 0.01% mixture of M. oleifera and A. indica at 68.15% and 49.63%, respectively. Based on the combination index (CI), all mixtures have synergistic joint action against N. lugens nymph except ratio 8:2 (C1=0). For ratio 1:9, 2:8, 3:7, 4:6, 5:5 6:4, 7:3 and 9:1 the CI were 0.0048, 0.0086, 0.0091, 0.019, 0.0133, 0.047, 0.0163 and 0.0379 respectively.